Prospects for the use of herbal medicine in the treatment of patients with non-alcoholic fatty liver disease - V. A. Akhmedov; T. I. Melikov (Лечащий Врач, 2021)
Lifestyle modification, which includes the following: a healthy diet and physical activity, along with weight reduction, remains the first line of treatment for non-alcoholic fatty liver disease (NAFLD). However, due to the poor adherence to this type of treatment, especially for long-term weight loss diets, some of which may have harmful effects on the liver, there is significant interest in identifying therapeutic agents for the treatment and/or prevention of NAFLD progression. Due to potential adverse effects of conventional medical therapies, the focus has been directed to studying complementary therapies that are both natural and safe, such as herbal medicine and functional foods as dry materials or their extracts.Those patients who fail to achieve goals with classical therapy are potential candidates for herbal nutraceuticals.However, it should be borne in mind that nutraceuticals are sold in the form of mixtures of various compounds, so their appointment is not always easy for the doctor. It is also necessary to assess the cost, long-term effects and potential risk of drug interactions for patients. When using purified phytochemicals, the above problems are greatly simplified compared to plant extracts. Although several clinical trials are currently underway to evaluate the therapeutic effect of nutraceuticals and plant products, it is anticipated that scientists will pay more attention to assessing the efficacy of herbal therapeutic agents in the future by conducting larger randomized clinical trials and carefully evaluating their results.